Engaging with Content and Language Using Student-created Blended Media - Garry Hoban (Bandar Lampung University (UBL), 2013)
Innovative approaches to teaching and learning are needed in schools and universities to provide new ways for students to engage with content and language. In particular, advances in personal digital technologies over the last 10 years enable students to create a variety of digital media forms such as podcasts, vodcasts, screencasts, videos, digital stories and animations using their own technologies such as smart phones and Ipads. Whilst each digital media form has its own affordances for learning and purpose, they can also be integrated or “blended” to provide new ways for students to make meaning and communicate. Blending digital media is especially engaging if students understand the features of particular genre and use their own technologies and select the most appropriate “blend” to provide a quality digital explanation.